Pengaruh Iradiasi Sinar Gama terhadap Pertumbuhan dan Regenerasi Kalus Padi Varietas Ciherang dan Inpari 13 - Rossa Yunita; Nurul Khumaida; Didy Sopandie; Ika Mariska (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2014)
Effect of gamma irradiation on rice callus dependson the irradiation dose used. Irradiation dose is one of thefactors that affect the genetic changes in the cells of plants.High doses can result in tissue death, meanwhile low doseswill result in abnormal changes in plant phenotype. The levelof sensitivity of a plant tissue against gamma irradiation isdifferent. This study aimed to evaluate the growth andregeneration of callus in various irradiation doses of gammaray. The plant materials used were mature embryos of ricevar. Ciherang and Inpari 13. This study used a completelyrandomized design with gamma irradiation treatment atdoses of 10, 20, 30, 40, 50, 60, 70, 80, 90, and 100 Gy. Eachtreatment consisted of 10 replicates with 5 embryogenic calliper bottle. The results showed that the increasing doses ofgamma irradiation increased the percentage of dead callus,inhibited callus growth, and its ability to regenerate. Thehigh percentages of callus of Ciherang and Inpari 13 thatformed green spots and adventitious shoots were mostlyobtained from controls. The percentages decreased atirradiation doses of 10, 20, 30, and 40 Gy. Moreover, the calliof Ciherang and Inpari 13 were not able to form adventitiousshoots at irradiation doses higher than 40 Gy and 30 Gy,respectively.